2016
DOI: 10.1515/pjvs-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of point mutations in exon 2 of GDF9 gene in Kermani sheep

Abstract: Screening the fertile ewes from national herds to detect the major genes for prolificacy is an effective way to create the fertile flocks. Growth differentiation factor (GDF) 9 is a member of the transforming growth factor β superfamily that is essential for folliculogenesis and female fertility. The aim of this study was to detect single nucleotide polymorphisms (SNPs) in exon 2 of GDF9 gene in Kermani sheep breed using PCR-SSCP. Genomic DNA was extracted from whole blood of collected samples using salting-ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…There are 26 sheep breeds in Iran, each having been adapted to a certain region (Khodabakhshzadeh et al, 2016;Zamani, Akhondi, & Mohammadabadi, 2015). Kermani sheep is one of the most important breeds of Iran's native sheep.…”
Section: Introductionmentioning
confidence: 99%
“…There are 26 sheep breeds in Iran, each having been adapted to a certain region (Khodabakhshzadeh et al, 2016;Zamani, Akhondi, & Mohammadabadi, 2015). Kermani sheep is one of the most important breeds of Iran's native sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Animal Sciences, v. 42, e47483, 2020 The studied populations were not found to be in a Hardy-Weinberg equilibrium. The reason for this could be more heterozygotes than homozygotes, mutation, migration, genetic drift and level of crossbreeding in some populations (Khodabakhshzadeh et al, 2016;Mohammadabadi et al, 2010). Although crossing native and commercial breeds can have a faster effect on improving native animal yield than long-term programs as a result, is more beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, Hanrahan et al (2004) observed eight polymorphisms in the entire coding region of the sheep GDF9 gene. Later investigation by Bahrami et al (2014) and Khodabakhshzadeh et al (2016) also detected some point mutations (SNP) in the GDF9 gene located in exon 1 and exon 2, respectively. Four mutations detected in the present study indicated that the GDF9 gene in Garut sheep was found to be polymorphic.…”
Section: Pcr Amplification and Snps Detectionmentioning
confidence: 96%
“…He et al (2010) found one point mutation of the GDF9 gene in Chinese goats that is associated with ovulation rate. Many significant associations have been reported between GDF9 polymorphism and ovulation rate, prolificacy, and fertility in sheep (Hanrahan et al 2004;Ghaffari et al 2010;Ghaderi et al 2010;Souza et al 2014;Mullen and Hanrahan 2014;Khodabakhshzadeh et al 2016;Ahmad et al 2017). Moreover, current investigations in sheep, humans, and rodents show that the GDF9 and BMP15 genes can be regarded as important genes associated with prolificacy in mammals (Mc-Natty et al 2005).…”
Section: Introductionmentioning
confidence: 99%